Speech balloon and speaker association for comics and manga understanding - Rigaud, Christophe; Nam Le Thanh; Burie, J-C; Ogier, J-M; Iwata, Motoi; Imazu, Eiki; Kise, Koichi (2015 13th International Conference on Document Analysis and Recognition (ICDAR), 2015)
Comics and manga are one of the most important forms of publication and play a major role in spreading culture all over the world. In this paper we focus on balloons and their association to comic characters or more generally text and graphic links retrieval. This information is not directly encoded in the image, whether scanned or digital-born, it has to be understood according to other information present in the image. Such high level information allows new browsing experience and story understanding (e.g. dialog analysis, situation retrieval). We propose a speech balloon and comic character association method able to retrieve which character is emitting which speech balloon. The proposed method is based on geometric graph analysis and anchor point selection. This work has been evaluated over various comic book styles from the eBDtheque dataset and also a volume of the Kingdom manga series.